Characterization of EM effects in RF/microwave integrated circuits - Yagoub, M.C.E.; Sharma, P. (34th European Microwave Conference 2004 : conference proceedings : Tuesday 12th, Wednesday 13th and Thursday 14th October, 2004)
Widely used in RF/microwave integrated circuits, passives are subject to intensive research for efficient modeling. At the circuit level, such devices are modeled either as lumped or as physicaVgeometrical based semi-analytical elements, which cannot adequately include all electromagnetic (EM) effects. On the opposite, although EM-based models are quite accurate, they cannot be easily implemented in a circuit simulator, and even though, such individual models did not include device coupling effects. This paper introduces, for the Jim lime, the concept of automatic generation of accurate and fast neural models for passives that can efficiently integrate higher-order EM coupling effects between various circuit elements. Plugged into commercial circuit simulators, the technique can predict no1 only the optimum geometrical structure of passives bur also their optimum placement into the circuit layout taking into account mutual device coupling.